Desenvolvimento de aplicações digitais para um congresso científico - Almeida, João Carlos Silva (2022)
This project aims to create a website for the XX AECA International Meeting. In this context, it presents the importance of scientific knowledge as a fundamental and inescapable step in science. The key to theis project was the development of an usable website to promote the XX International of the AECA, using the methodology proposed by Lynch & Horton in 2016. In order to captivate the audience was as well developed a mobile app to improve a better accessibility of the event. In addition, applying a validated scale was performed to measure the user experience of the website. As a result, in addition to website and mobile application development, the Reliability, Efficiency and Perspicuity constructs obtained significantly higher scores when compared to Attractiveness, Stimulation and Novelty, not differing from each other in a statistically significant way.